Optimizing Cash Waqf Management in Indonesia: Exploring Effective Models - ., suhairi (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2023)
Cash waqf management in Indonesia faces challenges due to the overload tasks of Sharia banks as the Sharia financial institution of cash waqf (SFI-CW). This research explored Sharia Bank's problems as an SFI-CW and looked for an effective model to manage cash waqf in Indonesia. The results of this research show that the existence of Sharia banks as SFI-CW has yet to be implemented optimally due to the overload tasks of the banks. To solve the problem and to make the cash waqf management run effectively, this study proposes some alternatives, including: first, simplifying the tasks of the SFI-CW; second, making the Baitul Maal wat Tamwil (henceforth BMT) or sharia cooperation as Nazhir of cash waqf as well as SFI-CW; and third, establishing waqf bank to optimize the management of cash waqf.